Strategi Marketing Mix pada Bisnis Tanaman Hias untuk Mencapai Keunggulan Bersaing Ditinjau dari Etika Bisnis Islam - Putri Rosyidah; Siswahyudianto (Idarotuna : Journal of Administrative Science, 2023)
The ornamental plant business has good profit prospects so that there are more and more enthusiasts day by day, so new strategies are needed in order to survive and respond to challenges in the midst of increasingly fierce competition. One way for Kebon Godonk's business to achieve competitive advantage is to understand and apply the concept of a marketing mix strategy. The aspect used is the marketing mix with 4P which consists of product, price, place, promotion. The purpose of this study is to evaluate the effectiveness of implementing the marketing mix strategy in achieving competitive advantage, taking into account the principles of Islamic business ethics. Researchers will evaluate the extent to which the marketing strategy has been implemented properly, therefore companies must be able to analyze to meet consumer needs so as to create consumer awareness and interest in related goods or services. The research method used is descriptive qualitative method. Methods of data collection, data reduction, data presentation, and drawing conclusions are also applied. Data validity will be tested using triangulation techniques. From the research that has been done, it shows that the implementation of the marketing mix strategy in Kebon Godonk is very influential in increasing this business so that it can develop and be able to compete with other entrepreneurs. The strategy carried out has also implemented the concepts of Islamic business ethics such as divinity, honesty, responsibility and justice.